Spatial heterogeneity of the physical properties of the soil in the floodplain of the small river - V. M. Yakovenko; J. J. Dubinina; Y. O. Zhukova (Agrology, 2019)
The features of the soil physical indices variation in the floodplain of small river were investigated in the present article. The role of tree stand spatial organization in the variation of soil properties was shown. The soil intersection was made in the oak forest in the river Protich floodplains. The experimental polygon was laid near the intersection, which consists of 105 points of measurement of the soil properties, which together form a grid of size 7×15. Distance between the measurement points was 3 m. Tree stand on the trial site was represented by 6 species of plants. The primary layer was presented by the Quercus robur L. and Ulmus laevis Pall., and Pyrus communis L. may be occasionally encountered. The understory was presented by the Acer tataricum L., Crataegus monogyna Jacq. and Euonymus europaeus L. The soil penetration resistance was 0.72 ± 0.01 MPa in the surface layer 0–5 cm. By the depth of 35–40 cm, the soil penetration resistance was not changed substantially, while the local maximum was observed at a depth of 15–20 cm. After a depth of 40–45 cm there was a rapid, practical linear, the growth of the soil penetration resistance with depth resulting in the soil penetration resistance at the depth of 95‒100 cm acquires value 3.69 ± 0.09 MPa. The soil electrical conductivity in the surface layer was 0.49 ± 0.06 dSm/m. Moisture content in the surface layer of soil at the time of the study was 3.58 ± 0.24% with a significant level of varying within the polygon (CV = 69.47%). The bulk soil density varied widely (from 0.33 to 1.48 g/cm3). In the aggregate structure, the macroaggregate of the size greater than 10 mm was dominated fraction (23.46 ± 0.98% from the total weight). The four principal components were extracted which together explain 48.28% variation of the soil characteristics. Regression model with the closest distances from individuals of forest plants to the points of accounting of the soil indices as predictors can explain 26% variation of the values of principal component 1. The Acer tataricum, Quеrcus rоbur and Pirus communis were revealed to be statistically significant predictors of this principal component. The distance to the trees was able to explain 33% variation of the principal component 2. The distances to the Crataegus laevigata, Ulmus laevis and Pirus communis were the most important predictors of this principal component. A variation of the principal component 3 by 47% can be explained by means of distances to trees. 56% of the principal component 4 variation can be explained using distances to trees. The principal component of the soil properties variation can be related with the most important elementary soil-forming processes within the investigated polygon, which is the basis for their spatial peculiarities of their distribution.